2015
DOI: 10.1093/aepp/ppv001
|View full text |Cite
|
Sign up to set email alerts
|

Too Busy to Eat with the Kids? Parental Work and Children's Eating

Abstract: Parents influence their children's eating behavior by providing access to certain types of food, creating enjoyable mealtimes and associations with food, and by role modeling. In this study we investigate the association between parental employment and parental time spent eating with their children. Using data from the 2001/02 German Time Budget Survey, we explore associations between time spent eating with children and labor force participation in Germany. We find that parental labor force participation is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…There is limited empirical evidence (Beatty et al, 2013; Chen et al, 2015; Eswaran et al, 2013; Mothersbaugh et al, 1993; Peterman et al, 2013) to test and corroborate the linkages between time use and nutritional outcomes of individuals. This could be due to lack of micro-level data on the nutritional status of women and children, and women's time use in agriculture and domestic work.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited empirical evidence (Beatty et al, 2013; Chen et al, 2015; Eswaran et al, 2013; Mothersbaugh et al, 1993; Peterman et al, 2013) to test and corroborate the linkages between time use and nutritional outcomes of individuals. This could be due to lack of micro-level data on the nutritional status of women and children, and women's time use in agriculture and domestic work.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, according to the results of this study, it was found that married people spend 14.3 percentage points more time on housework and childcare than all employed persons. In addition, interesting findings have been made by researchers Chen et al (2015) investigating the German labour market: the more time parents spend on work, the less time parents spend on children.…”
Section: Employed Personsmentioning
confidence: 99%
“…Orang tua yang bekerja memiliki lebih sedikit waktu makan bersama anaknya, dimana seharusnya berperan penting membentuk perilaku makan anak. Ibu tentunya merupakan orang tua yang berperan aktif membentuk perilaku makan anak (Chen, Möser, & Nayga, 2015). Pekerjaan orang tua melalui tingkat pendapatan dan pola makan anak dengan demikian dapat memengaruhi kebiasaan makan anak yang secara tidak langsung berdampak pada status iodium anak.…”
Section: Karakteristik Sosial Ekonomi Orang Tuaunclassified